Evaluating genetic diversity of chilling stress in cotton genotypes - Sofalian, Omid; Azimy, Somayyeh; Jahanbakhsh, Sodabeh; Khomari, Saeid; Dezhsetan, Sara (Plant Breeding and Seed Science, 2013)
In order to study genetic diversity and some physiological features related to chilling stress using molecular markers, an experiment was conducted at University of Mohaghegh Ardabili. Treatments were set in a factorial experiment based on randomized complete block design with 3 replications and 3 stress levels (25, 15 and 5°C) between 20 cotton genotypes. The results showed that chilling stress influenced on some physiological features such as the activity of catalase, proline content, soluble carbohydrates and proteins. Cluster analysis carried out using WARD method in physiological features showed that genotypes located in three groups in the acclimation level and after acclimation, respectively. Nazilli, Ciakra, Avangard and B 557 were in the better group in studied levels. Also based on the results Avangard, Chegurava, Tashkand and Shirpan 603 were the most tolerant genotypes. In the ISSR marker analysis using of 12 primers produced 96 polymorphic bands. The mean of PIC, MI and EMR were 0.283, 1.065 and 3 respectively, for all primers. Some of markers had promising results that confirmed ISSR markers as powerful tool in any marker assisted program for plant breeders.